ANSWER
(4, -1) or (-1, -6)
Step-by-step explanation
Given that;
![\begin{gathered} \text{ y = x - 5 ------ equation 1} \\ \text{ y = x}^2\text{ - 2x - 9 ---- equation 2} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/jdj8kmr34cmiffuqoqizjy4jvtqcqrrjaz.png)
Follow the steps below to find the value of x and y
Step 1; Equate equation 1 and 2 together
![\begin{gathered} \text{ x - 5 = x}^2\text{ - 2x - 9} \\ \text{ x}^2\text{ - 2x - 9 - x + 5 = 0} \\ \text{ x}^2\text{ -2x - x - 4= 0} \\ \text{ x}^2\text{ - 3x - 4= 0} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/zubrn0w6die72a1veel0du0tx338ph2zt4.png)
Step 2; factorize the above quadratic equation above
![\begin{gathered} \text{ x}^2\text{ - 3x - 4 = 0} \\ \text{ x}^2\text{ -4x + x -4 = 0} \\ \text{ x\lparen x - 4\rparen + 1 \lparen x - 4\rparen= 0} \\ \text{ \lparen x - 4\rparen = 0 or \lparen x + 1 \rparen = 0} \\ \text{ x = 4 or x = -1} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/uybwdbkhkekos3fd8325tjnllodclighvv.png)
Step 3; Find the values of y by substituting the values of x into equation 1
![\begin{gathered} \text{ y = x - 5} \\ \text{ x1 = 4 and x2 = -1} \\ \text{ y1 = 4 - 5} \\ \text{ y1 = -1} \\ \\ \text{ y2 = x2 - 5} \\ \text{ y2 = -1 - 5} \\ y2\text{ = -6} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/n4v8qkft5yerlg393ccduslw7tht23kz58.png)
Therefore, we have (4, -1) or (-1, -6)